Breast and thyroid cancer: A multicenter study with Accrual to Clinical Trials Network. Issue 8 (23rd February 2022) - Peckham, Merry; Spencer, Horace J.; Syed, Shorabuddin; Armstrong, William B.; Farwell, Donald Gregory; Gal, Thomas J.; Goldenberg, David; Russell, Marika D.; Solis, Roberto N.; King, Deanne; Stack, Brendan C.
Abstract: Objective: To investigate a possible link between breast and thyroid cancer. Methods: A multicenter retrospective review of patients in the electronic medical records of six Accrual to Clinical Trial (ACT) institutions with both breast cancer and thyroid carcinoma. Each center queried its data using a predefined data dictionary. Information on thyroid and breast cancer included dates of diagnosis, histology, and patient demographics. Results: A random‐effects model was used. There were 4.24 million women's records screened, 44 605 with breast cancer and 11 846 with thyroid cancer. The relative risks observed at each institution ranged from 0.49 to 13.47. The combined risk ratio (RR) estimate was 1.77 (95% confidence interval: 0.50–5.18). Conclusion: There was no association between the risk of developing thyroid cancer and being a breast cancer survivor compared to no history of breast cancer, but the range of relative risks among the participating institutions was wide. Our findings warrant further study of more institutions with larger sample size. Additionally, further analysis of the significance of regional RR differences may be enlightening.